2014
DOI: 10.1016/j.stem.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Frequencies of Coding Mutations and Loss of Imprinting in Human Pluripotent Cells Derived by Nuclear Transfer and Defined Factors

Abstract: The recent finding that reprogrammed human pluripotent stem cells can be derived by nuclear transfer into human oocytes as well as by induced expression of defined factors has revitalized the debate on whether one approach might be advantageous over the other. Here we compare the genetic and epigenetic integrity of human nuclear-transfer embryonic stem cell (NT-ESC) lines and isogenic induced pluripotent stem cell (iPSC) lines, derived from the same somatic cell cultures of fetal, neonatal, and adult origin. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 36 publications
7
114
2
Order By: Relevance
“…Both iPS cells and ntES cells showed more de novo coding mutations, 10 on average, than parthenogenetic stem cell lines with a germ line origin, which contained 1.25 de novo mutations [19 ].…”
Section: Functional Tests Expose Differences In Stem Cell Qualitymentioning
confidence: 96%
See 2 more Smart Citations
“…Both iPS cells and ntES cells showed more de novo coding mutations, 10 on average, than parthenogenetic stem cell lines with a germ line origin, which contained 1.25 de novo mutations [19 ].…”
Section: Functional Tests Expose Differences In Stem Cell Qualitymentioning
confidence: 96%
“…Johannesson and colleagues compared human ntES cell lines to iPS cell lines derived from the same somatic cell cultures of fetal, neonatal, and adult origin [19 ]. The two cell types of ntES and iPS cell lines showed no systematic differences in gene expression and DNA methylation patterns.…”
Section: Highs and Lows In Somatic Cell Nuclear Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…They found that iPSCs have aberrant DNA methylation statuses for some imprinted genes, such as DIRAS3, MEG3 and PEG3, and regions of X-chromosome inactivation. However, Johannesson et al concluded that human SCNT-ESCs and iPSCs have no significant differences in gene expression, DNA methylation or frequency of de novo coding mutations [81]. In addition, imprinting loss was shown to occur in both SCNT-ESC and iPSC lines with a similar frequency.…”
Section: The Challenges Of Induced Pluripotent Stem Cells (A) Diversimentioning
confidence: 99%
“…Due to the considerable costs of these tests, the stem cells community should agree on the minimal standard requirements for legitimate research purposes. However, we strongly advocate for a rigorous and more in-depth analysis of iPSC lines for clinical applications to identify genetic and epigenetic alterations, including mitochondrial DNA mutations (15) copy number variations (CNVs) (16) and histone tail modifications (17), at least until we achieve a clear understanding of the safety profile. Of note, the first clinical trial using iPSC-derived cells was put on hold because the genetic analysis revealed presence of new CNVs in the cells differentiated for transplantation.…”
mentioning
confidence: 99%